Physiological and Biochemical Impacts of Gestational Diabetes on Maternal and Fetal Health: A Systematic Review: Physiological and Biochemical Impacts of Gestational Diabetes on Maternal and Fetal Health - Mahmood, Anjum; Ishaq, Bibi Hajira; Khalid, Maham; Zahra, Sadaf; Javed, Qaiser; Ijaz, Azhar (Pakistan Journal of Health Sciences, 2026)
Gestational diabetes mellitus is increasingly recognized as more than a transient elevation of blood glucose during pregnancy. Evidence suggests that GDM represents a broader metabolic disturbance involving chronic low-grade inflammation, dyslipidemia, oxidative stress, endothelial dysfunction, and adipokine imbalance. These alterations appear to influence not only maternal metabolic health but also fetal growth and early developmental outcomes. Objectives: To synthesize recent evidence (2017–2024) on physiological and biochemical changes associated with GDM and to examine their implications for maternal and fetal health. Methods: A systematic literature search was conducted across PubMed, Scopus, Web of Science, and ScienceDirect in accordance with PRISMA 2020 guidelines. Original human studies comparing GDM and normoglycemic pregnancies were included if they assessed metabolic, inflammatory, oxidative, vascular, or endocrine biomarkers. Study quality was evaluated using the National Institutes of Health quality assessment tools for observational studies and the Cochrane Risk of Bias 2 tool for randomized trials. Due to heterogeneity in study design and outcome measures, findings were synthesized narratively. Results: Thirteen studies met the inclusion criteria. GDM was consistently associated with elevated inflammatory markers (hs-CRP, IL-6, IL-18), increased triglycerides, oxidative stress markers such as malondialdehyde, and reduced adiponectin and antioxidant enzymes. Maternal hypertriglyceridemia independently predicted fetal macrosomia, while elevated umbilical cord C-peptide reflected fetal hyperinsulinemia. Nutritional interventions, including DHA supplementation, showed favorable modulation of selected adipokines. Conclusions: The evidence supports GDM as a systemic metabolic disorder characterized by interconnected disturbances in glucose, lipid, inflammatory, and oxidative pathways, with important maternal and fetal implications.